Pengembangan Bahan Ajar Akuntansi Berbantuan Microsoft Excel untuk Meningkatkan Pemahaman Siklus Akuntansi - Agustiawan, Try Darma; Khoirunnisa, Nafilah; Budiman, Muhammad Akbar; Koryati, Dewi (SAP (Susunan Artikel Pendidikan), 2024)
Traditional accounting teaching materials tend to be less engaging and do not always integrate practical approaches that can motivate students to understand the accounting cycle as a whole. The aim of this research is to produce a valid and practical teaching materials that can increase understanding of the accounting cycle with the help of Microsoft Excel software. This research is R&D research with the ADDIE model. The subjects of this study were 4th semester students of the Economic Education Study Program, FKIP, Sriwijaya University. Data was collected over a period of 4 months and obtained through the Needs Analysis Questionnaire, Validity Questionnaire, Practicality Questionnaire, and Test Questions.. The research results show that the teaching materials developed have met the Valid criteria with a percentage of 92.3% which is included in the Very Valid criteria. This teaching material is also considered practical with a percentage of 84% which is included in the Practical criteria. Apart from that, based on the results of calculating the N-gain value, it was found that this teaching material can improve understanding of the accounting cycle with an average N-gain of 0.98 which is included in the effective criteria. Based on the results obtained, the resulting teaching materials are highly recommended for use in increasing understanding of the accounting cycle. Experimental studies can also be carried out to see whether there is an influence on students' understanding of the accounting cycle before and after using this teaching material.